The investigation of the manufacturing technology influence on the wine-making materials of different regions of Ukraine - Turash, V.; Babich, Irina (My University, 2014)
In modern manufacturing circumstances, when different types of the wine-making manufacturing technologies and different finning materials are used, the aim of the investigation is to analyse the influence of the enogelatin (domestic manufactured) on the quality of the wine-making materials and their permanence.
Keywords: enogelatin; аргозин; еножелатин; кафедра біотехнології продуктів бродіння і виноробства